Cooperation of enterprises in the sphere of human resources in logistics - Hanus, Piotr; Kasperek, Marek (Współpraca przedsiębiorstw w sferze zasobów ludzkich w logistyce, 2019)
Human resources are an important factor in logistics. Their lack of or gaps in competence development cause serious consequences. The aim of the article is to indicate the main factors that may shape the sphere of human resources in logistics, their importance and the need to develop cooperation between enterprises in this area. This study is exploratory (literature studies, internet resources). The subject matter is also the result of the author’s research and the LOGOS scientific research project. The content of the article is based on analysis of the factors that have been identified in the source materials. The principle of comparing and searching for analogous subjects in the sources has been adopted. The most important conclusion drawn from the content is to ensure the development of human resources in logistics and to develop cooperation due to the emerging challenges of staff shortages and the development of new technologies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 141-151
Keywords: cooperation; human resources; logistics; współpraca; zasoby ludzkie; logistyka